-643C > T RANKL gene polymorphism is associated with osteoporosis in Tunisian postmenopausal women. (4th July 2017) - Sassi, R.; Sahli, H.; Cheour, E.; Sellami, S.; El Gaaied, A. Ben Ammar
Abstract: Objectives: The dynamic nature of the skeleton is achieved by a remodeling process. Receptor activator of nuclear factor kappa B (RANK) ligand (RANKL) stimulates bone resorption by activating RANK signaling. Therefore it is considered as a candidate gene regulating susceptibility to osteoporosis. In the current study, we have investigated the association between the RANKL gene -693G > C and -643 C > T polymorphisms and bone mineral density (BMD) in a population of postmenopausal Tunisian women. Methods: Polymorphic sites in RANKL gene (rs9533155 -693G > C and rs9533156 -643 C > T polymorphisms) were determined using PCR-RFLP analysis in 566 postmenopausal Tunisian women. All statistical analysis were examined by SPSS software. Results: We have detected a significant difference in lumbar spine and hip BMD for -643C > T genotypes. For -693G > C genotypes, a significant difference was detected only in hip BMD. The distribution of -643C > T genotypes and alleles between three groups (osteoporotic, osteopenic and normal women) revealed a significant association of the TT genotype with development of osteoporosis ( p  = 0.01; odds ratio 2.15), although for the -693G > C polymorphism, no significant results were found. Conclusion: We have demonstrated the association of the -643C > T polymorphism with BMD variation and osteoporosis risk in postmenopausal Tunisian women.